A Simple Solution of Dissolved Ammonia Recovery Process in a Hollow-Fiber Membrane Contactor: Comparison with Experimental and Numerical Results - Hassan, Eman W.; Chaalal, O.; Hossain, Md Monwar (Journal of Membrane and Separation Technology, 2019)
Ammonia in gaseous form is one of the major pollutants in waters and wastewaters. Of all the processes studied so far for the removal of dissolved ammonia from aqueous solution, hollow fiber membrane contactor-based processes have shown great potential. This method has shown to be effective to substantially reducing ammonia concentration to an acceptable value economically and efficiently. Mathematical analysis is presented in this report for the removal of ammonia dissolved in an aqueous phase to a recovery/stripping solution in a hollow fiber membrane contactor (HFMC). The membrane contactor is considered to consist of the lumen side (allowing aqueous flow) and shell side (allowing the flow of the stripping/recovery solution). An approximate analytical solution is derived for the simplified model that does not include radial diffusion of solutes (only axial mass flux is included). The predicted results of this solution are compared with the experimental data and with the numerical results in the literature over a range of operating conditions. The flow rates of the feed solution covered: 2.01 x 10 -9 to 4.7 x 10 -6 m3/s, initial concentration: 50 – 800 ppm and pH values of the solution containing ammonia: 8 - 11. The agreement is very good between the profiles of the simplified analytical solution and the earlier published experimental data. In addition, the results obtained by the analytical solution are close to the numerical solution of the complete model over a good range of operating conditions.